Learning about the effectiveness of teacher education: a Chilean study - Avalos, Beatrice; Téllez, Francisco; Navarro, Silvia (Faculty of Education, University of the Free State, 2010)
The article reviews some of the problems faced by teacher education in general and in Chile specifically, and on this basis, presents the results of a study focused on the effects of six teacher education programmes on future primary level teachers’ learning of mathematics and mathematics pedagogy. The study describes the programmes and presents the results of a questionnaire and content knowledge test administered to future teachers in their first, third and final year of studies. The article considers as possible explanations for unsatisfactory effects of teacher preparation on future teacher learning, the relatively poor entry levels of student teachers and the generalist structure of the programmes. Differences among programmes between time allocation to mathematics and mathematics pedagogy learning did not appear to have an effect. Specific courses, however, did appear to make a difference among institutions.
Keywords: Teacher education; Mathematics and mathematics pedagogy content knowledge; Curriculum; Teaching-learning strategies; Programme effectiveness; Education, Chile